Synergistic Therapy of Celecoxib-Loaded Magnetism-Responsive Hydrogel for Tendon Tissue Injuries - Wang, Jingxin; Wang, Likang; Gao, Yueming; Zhang, Zhao; Huang, Xiaofeng; Han, Tong; Liu, Biyuan; Zhang, Yujie; Li, Yilan; Zhang, Lining (Frontiers in Bioengineering and Biotechnology, 2020)
Tendon tissue injury is very common and always associated with pain, tissue swelling and even malformation if not treated on time. Traditional therapeutic strategies, such as cryotherapy, electrical therapy, ultrasound therapy and anti-inflammatory drug, are still unsatisfying. In this work, a synergistic therapy, based on the combination of celecoxib drug and pulsed electromagnetic field (PEMF) regimens, was developed for the treatment of tendon injury. This celecoxib-loaded magnetism-responsive hydrogel dressing (gelatin/Fe3O4/celecoxib) showed good biocompatibility and coordinated drug release behavior under the PEMF, which could effectively reduce the inflammatory reaction of macrophage cells with the incremental proportion of M2 macrophages at the injury site. CatWalk gait analysis further verified this synergistic effect of combination therapy for achieving the outstanding recovery of the injured tendon tissue. Thus, this magnetism-responsive hydrogel may represent a promising alternative strategy in clinics for promoting tendon healing.